Fiscal transfers and common debt in a Monetary Union: A multi-country agent based-stock flow consistent model - Alessandro Caiani; Ermanno Catullo (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2023)
Using a refined version of the multi-country AB-SFC model of a Monetary Union already presented in Caiani et al. (2018a, 2019) the paper aims at providing a tentative assessment of the economic effects of transforming the European Monetary Union into an Intergovernmental Fiscal Transfer Union (IFTU) with its own fiscal capacity. Countries contribute proportionally to their GDP whereas funds are redistributed according to a mechanism that gives more funds to countries performing worse than the average of the Union in cyclical terms. Our simulations show that an IFTU inspired by such a redistribution principle acts as a stabilizer of international trade, allowing to stabilize and improve the Union GDP performance without affecting the stability of public finances. When the Union is allowed to borrow on capital markets, i.e. in a Fully-Fledged Fiscal Transfer Union (FFFTU), these effects are enhanced and a part of the public debt burden shifts from the national to the Union level, leaving the total burden almost stable. An interesting result to assess the political acceptability of the proposal is that 'core' countries eventually benefit the most from the introduction of this mechanism, despite being more frequently net contributors. Finally, we show that an FFFTU with common debt might help to soften the impact of an exogenous demand shock while, because of the fact that it mainly operates as a stabilizer of aggregate demand, it does not seem to provide beneficial effects when facing a supply shock to production.
Keywords: F45; F41; C63; 330; Fiscal Transfer Union; Union Bonds; European Integration; Agent Based Macroeconomics; Stock Flow Consistent Models